Possible Association between the Quantity of Peri-implant Crevicular Fluid, Clinical Indices, and the Dimensions of Endosseous Implants - Onurcem Duruel; Samir Goyushov; Nil Yakar; Güliz Nigar Güncü; Erdem Karabulut; Tolga Fikret Tözüm (Stilus Optimus, 2022)
Objectives: The objectives of this clinical observational study are to measure peri-implant crevicular fluid volume based on dental implant diameter and length, and to evaluate the possible relationship between peri-implant crevicular fluid/gingival crevicular fluid volumes and clinical periodontal indices. Material and Methods: The information about length and diameter of dental implants was noted. Clinical indices (probing depth, plaque index, gingival bleeding time index, and gingival index) were recorded. Peri-implant crevicular fluid (PICF)/gingival crevicular fluid (GCF) volumes were measured from 4 sites (mesial, buccal, distal, and lingual/palatal) of each dental implant including its one or more equivalent natural tooth/teeth. Results: One-hundred-sixty-one loaded dental implants and 221 natural teeth of 101 patients were evaluated. The length of dental implant had no effect on PICF volume (P > 0.05). However, PICF volumes of narrow (< 3.5 mm) and wide (> 4.5 mm) diameter implants were higher than standard diameter implants (≥ 3.5 mm, and ≤ 4.5 mm) (P < 0.05). PICF and GCF volumes of areas with peri-implant/periodontal diseases were significantly higher than healthy areas (P < 0.05). PICF and GCF volumes showed positive correlations with clinical indices (P < 0.05). Conclusions: In accordance with the results of the present study, the implant diameter, not the implant length, affects peri-implant crevicular fluid volume.